Knowledge and Attitude toward Tuberculosis among Tuberculosis Patients Seeking Help in Diagnostic and Treatment Centers, Kabul Province in Afghanistan - Assadullah Rasooli; Elham Ahmadnezhad; Keramt Nouri Jelyani; Kourosh Holakouie-Naieni (Tehran University of Medical Sciences, 2015)
No Abstract